Down-Regulation of Plasma Intrinsic Protein1 Aquaporin in Poplar Trees Is Detrimental to Recovery from Embolism . Issue 4 (26th February 2014) - Secchi, Francesca; Zwieniecki, Maciej A.
Abstract : Aquaporins are involved in the maintenance of xylem transport system capacity, they promote recovery from stress, and they contribute to the control of stomatal conductance under water stress . Abstract: During their lifecycles, trees encounter multiple events of water stress that often result in embolism formation and temporal decreases in xylem transport capacity. The restoration of xylem transport capacity requires changes in cell metabolic activity and gene expression. Specifically, in poplar ( Populus spp.), the formation of xylem embolisms leads to a clear up-regulation of plasma membrane protein1 (PIP1) aquaporin genes. To determine their role in poplar response to water stress, transgenic Populus tremula × Populus alba plants characterized by the strong down-regulation of multiple isoforms belonging to the PIP1 subfamily were used. Transgenic lines showed that they are more vulnerable to embolism, with 50% percent loss of conductance occurring 0.3 MPa earlier than in wild-type plants, and that they also have a reduced capacity to restore xylem conductance during recovery. Transgenic plants also show symptoms of a reduced capacity to control percent loss of conductance through stomatal conductance in response to drought, because they have a much narrower vulnerability safety margin. Finally, a delay in stomatal conductance recovery during the period of stress relief was observed. The presented results suggest that PIP1 genes are involved in the maintenance of xylem transport system capacity, in the promotion of recovery from stress, and in contribution to a plant's control of stomatal conductance under water stress.